Use of the transoral robotic surgery to treat patients with recurrent lingual tonsillitis. Issue 4 (2nd April 2020) - Di Luca, Milena; Iannella, Giannicola; Montevecchi, Filippo; Magliulo, Giuseppe; De Vito, Andrea; Cocuzza, Salvatore; Maniaci, Antonino; Meccariello, Giuseppe; Cammaroto, Giovanni; Sgarzani, Rossella; Ferlito, Salvatore; Vicini, Claudio
Abstract: Background: This study evaluates the efficacy of lingual tonsil resection by transoral robotic surgery (TORS) in a large group of patients with recurrent lingual tonsillitis (RLT). Methods: Eighty‐four patients with RLT treated with a lingual tonsil surgical resection using TORS were analyzed in terms of their postoperative results, disease recurrence, postoperative dysphagia, and quality of life. Results: A reduction of the mean number/year of acute lingual tonsillitis (LT) episodes emerged after surgery (5.17 vs 0.54 events), comparing the mean number of preoperative and postoperative LT episodes, a statistical significance emerged ( P = .0001). The postoperative endoscopic evaluation showed 94.1% of patients with absent or poor lymphatic tissue on the tongue base. Evaluation of postoperative dysphagia showed good results with an average score of 85.9 ± 7.5. Conclusion: This article explains how in patients with chronic LT with medical therapy failure and impaired quality of life, TORS could represent a valid therapeutic option.